2007
DOI: 10.1016/j.virol.2007.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitination and proteasomal degradation of interferon regulatory factor-3 induced by Npro from a cytopathic bovine viral diarrhea virus

Abstract: The pathogenesis of bovine viral diarrhea virus (BVDV) infections is complex and only partly understood. It remains controversial whether interferon is produced in cells infected with cytopathic(cp) BVDVs which do not persist in vivo. We show here that a cpBVDV (NADL strain) does not induce interferon responses in cell culture and blocks induction of interferon-stimulated genes by a super-infecting paramyxovirus. cpBVDV infection causes a marked loss of interferon regulatory factor 3 (IRF-3), a cellular transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
128
1
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(139 citation statements)
references
References 61 publications
3
128
1
5
Order By: Relevance
“…It interacts with cellular proteins involved in viral genome transcription and replication (31). Furthermore, N pro has been shown to play a role in pestivirus-mediated inhibition of the IFN antiviral response (32,33). Because N pro regulates multiple processes in the life cycle of CSFV, we reasoned that it must interact with multiple host cell proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It interacts with cellular proteins involved in viral genome transcription and replication (31). Furthermore, N pro has been shown to play a role in pestivirus-mediated inhibition of the IFN antiviral response (32,33). Because N pro regulates multiple processes in the life cycle of CSFV, we reasoned that it must interact with multiple host cell proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The roles performed by the N-terminal protease N pro , namely the suppression of IFN production via the degradation of IRF-3 and suppression of dsRNA-induced apoptosis, have recently been described (Bauhofer et al, 2007;Chen et al, 2007;Gil et al, 2006;Hilton et al, 2006;Meyers et al, 2007;Ruggli et al, 2003Ruggli et al, , 2005Schweizer & Peterhans, 2001;Seago et al, 2007). The CSFV genome encodes a limited number of viral proteins and it is reasonable to expect that N pro interacts and modulates the host-cell machinery at different levels to ensure virus survival.…”
Section: Discussionmentioning
confidence: 99%
“…The CSFV genome, like those of other members of the genus Pestivirus, encodes an N-terminal cysteine-like autoprotease termed N pro that cleaves itself from the core protein and hence from the polyprotein chain. N pro has recently been shown to inhibit the production of type I IFNs by targeting IFN regulatory factor 3 (IRF-3) for proteasomal degradation (Bauhofer et al, 2007;Chen et al, 2007;Hilton et al, 2006;Seago et al, 2007).…”
Section: Classical Swine Fever Virus (Csfv) Is a Member Of The Genusmentioning
confidence: 99%
“…Moreover, the fact that virus infection prevented Mx induction and at the same time led to the complete disappearance of IRF-3 suggested that the effect of intact virus may be independent of E rns . Previous work has suggested that the effect on IRF-3 of pestiviruses may be mediated through N pro , which targets IRF-3 for proteasomal degradation (Bauhofer et al, 2007;Chen et al, 2007;Hilton et al, 2006; Seago et al, 2007).To assess the functions of the two proteins in the context of intact virus, rather than being expressed as single proteins, we made use of viral mutants lacking either N pro or the RNase activity of E rns (H30F). As shown previously (Schweizer & Peterhans, 2001), Mx (and hence IFN) production induced by extracellular and intracellular dsRNA was completely inhibited in cells infected with wt BVDV (Fig.…”
mentioning
confidence: 99%
“…Moreover, the fact that virus infection prevented Mx induction and at the same time led to the complete disappearance of IRF-3 suggested that the effect of intact virus may be independent of E rns . Previous work has suggested that the effect on IRF-3 of pestiviruses may be mediated through N pro , which targets IRF-3 for proteasomal degradation (Bauhofer et al, 2007;Chen et al, 2007;Hilton et al, 2006; Seago et al, 2007).…”
mentioning
confidence: 99%